2006
DOI: 10.1152/japplphysiol.01414.2005
|View full text |Cite
|
Sign up to set email alerts
|

Arginine-vasopressin mediates central and peripheral glucose regulation in response to carotid body receptor stimulation with Na-cyanide

Abstract: Arginine-vasopressin mediates central and peripheral glucose regulation in response to carotid body receptor stimulation with Na-cyanide. J Appl Physiol 100: 1902-1909, 2006. First published February 23, 2006 doi:10.1152/japplphysiol.01414.2005.-Hypoxic stimulation of the carotid body receptors (CBR) results in a rapid hyperglycemia with an increase in brain glucose retention. Previous work indicates that neurohypophysectomy inhibits this hyperglycemic response. Here, we show that systemic arginine vasopressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…The functional significance of OT neurosecretory neuronal activation in relation to cardiovascular responses associated with the chemoreflex remains at present unknown. It is worth mentioning that previous reports documented increased levels of both OT and VP neuropeptides following chemoreflex activation (Share and Levy, 1966; Chen and Du, 1999; Montero et al, 2006). …”
Section: – Discussionmentioning
confidence: 80%
“…The functional significance of OT neurosecretory neuronal activation in relation to cardiovascular responses associated with the chemoreflex remains at present unknown. It is worth mentioning that previous reports documented increased levels of both OT and VP neuropeptides following chemoreflex activation (Share and Levy, 1966; Chen and Du, 1999; Montero et al, 2006). …”
Section: – Discussionmentioning
confidence: 80%
“…With regard to the first possible mechanism, the central AVP/V1a receptor signal in the CNS regulates hepatic glucose production. AVP administration into the NTS or cisterna magna induced hyperglycemia (347,464,542). It has also been reported that AVP stimulates GABAergic neurons in vitro (214) and that GABAergic neurons suppress hepatic glucose production (259).…”
Section: V1a Receptor and Glucose Homeostasismentioning
confidence: 95%
“…In addition, direct carotid chemoreceptor stimulation by sodium cyanide was shown to increase hepatic glucose output and increase brain glucose retention within 2 to 8 min, via an adrenal gland- and sinus nerve-dependent manner (35). This same group subsequently demonstrated that the increase in plasma glucose following chemostimulation was mediated via activation of hepatic arginine vasopressin V1a receptors (594) and have since identified both an nNOS-activated mechanism in the hypothalamopituitary axis (125) and a GABA B -mediated mechanism in the nucleus tractus solitarius (518) that may be involved in the regulation of brain and plasma glucose levels following chemoreceptor stimulation. Similarly, intracarotid injections of glucose could significantly attenuate the normal hormonal response to hypoglycaemia (293), although these authors did not consider the reflex to originate from peripheral receptors in the carotid sinus region.…”
Section: Other Physiological Stimuli Of the Carotid Bodymentioning
confidence: 99%